2020
DOI: 10.3389/fmars.2020.00200
|View full text |Cite
|
Sign up to set email alerts
|

Meiofauna Community in Soft Sediments at TAG and Snake Pit Hydrothermal Vent Fields

Abstract: The risk assessment of seafloor massive sulfide (SMS) mining on meiobenthic organisms, specifically on soft-sediment meiofauna, is impeded by a lack of knowledge on the biology and ecology of these communities. In this study, we investigated sediment samples taken in proximity of active vents at Trans-Atlantic Geotraverse (TAG) and Snake Pit, two hydrothermal vent fields of the Mid-Atlantic Ridge, in order to explore metazoan meiofauna, particularly nematode community, and its relation to organic carbon, total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Recently, however, Cruz et al (2022) referred to a general similarity between the Broken Spur fauna and that encountered elsewhere on the MAR. As reported by Boschen-Rose and Colaco (2021), as few as 9 benthic megafaunal Gebruk and Mironov, 2006;Flint, 2007;Ivanenko et al, 2011;Tchesunov, 2015;Zeppilli et al, 2015;Sarrazin et al, 2015;Zeppilli et al, 2019;Spedicato et al, 2020); +, taxon recorded; -, taxon not recorded.…”
Section: Mega-and Nektobenthosmentioning
confidence: 64%
See 2 more Smart Citations
“…Recently, however, Cruz et al (2022) referred to a general similarity between the Broken Spur fauna and that encountered elsewhere on the MAR. As reported by Boschen-Rose and Colaco (2021), as few as 9 benthic megafaunal Gebruk and Mironov, 2006;Flint, 2007;Ivanenko et al, 2011;Tchesunov, 2015;Zeppilli et al, 2015;Sarrazin et al, 2015;Zeppilli et al, 2019;Spedicato et al, 2020); +, taxon recorded; -, taxon not recorded.…”
Section: Mega-and Nektobenthosmentioning
confidence: 64%
“…The soft sediment-covered areas away from active venting support fairly abundant meiobenthic communities compared with abundances found in other deep-sea environments. Abundances at the TAG and Snake Pit hydrothermal vent fields are 11-35 and 72-86 ind/10cm 2 respectively (Spedicato et al, 2020).…”
Section: Abundance and Biomassmentioning
confidence: 94%
See 1 more Smart Citation
“…Despite their ecological importance, the lack of reliable identification tools at lower taxonomical levels hampers ecological, molecular, and conservation studies ( Macheriotou et al, 2019 ; Ridall & Ingels, 2021 ; Pantó et al, 2021 ). As a result, nematodes are often identified at the genus level rather than the species level ( Miljutin et al, 2010 ; Sandulli, Semprucci & Balsamo, 2014 ; Brannock et al, 2017 ; Spedicato et al, 2020 ). The use of ML techniques in nematode identification is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Benthic species composition in sediments surroundings Rainbow is different compared to control deep-sea sediments and highly influenced by the vent plume's fall out (Klunder et al, 2020). Nematode community composition in sediments in the surroundings of Snake Pit and TAG vent fields on the Mid-Atlantic Ridge is hypothesized to be influenced by geochemical setting and food availability (Spedicato et al, 2020). A study in the northern West-Pacific, suggested that the effect of in situ derived organic matter as a food source near vents may be limited to at most several 100 m away from the venting area (Nomaki et al, 2019).…”
Section: Introductionmentioning
confidence: 99%